A new fabrication process of pedestal waveguides based on metal dielectric composites of Yb3+ /Er3+ codoped PbO-GeO2 thin films with gold nanoparticles - Bomfim, Francisco A. (2018)
This work reports the signal enhancement of Yb3+/Er3+ codoped PbO-GeO2 pedestal waveguides due to gold nanoparticles deposited over the core layer. The pedestal structure was obtained by conventional photolithography and plasma etching with a new procedure that does not use metallic hard-masks that normally introduce roughness, leading to light scattering. This new procedure brings advantages that benefit light guiding, reducing the propagation losses. Yb (3+)/Er3+ codoped PbO-GeO2 thin film was obtained by RF Magnetron Sputtering deposition and was used as core layer (410 nm height). In order to cover the core with gold nanoparticles the sputtering technique was used, followed by annealing at 400 degrees C during 1 h. The minimum propagation losses obtained were of 1.0 dB/cm at 1068 nm. Scanning Electron Microscopy (SEM) was employed for the waveguides structure inspection and transmission electronic microscopy (TEM) was used to verify the presence of gold nanoparticles on the waveguides. It was observed an enhancement of 180% for the relative gain that reached 7.8 dB/cm at 1530 nm, for an optical waveguide with 6 pm core width, under 980 nm excitation (pump power of 60 mW), attributed to the local field enhancement in the vicinity of the gold nanoparticles. The new fabrication process presented in this work opens possibilities for optical amplifiers with low propagation losses based on different metal dielectric composites, as well as other waveguide-based devices.